2015
DOI: 10.1186/s13567-015-0277-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immune responses against Psoroptes ovis in two cattle breeds with different susceptibility to mange

Abstract: The sheep scab mite, Psoroptes ovis, is a major problem in the beef cattle industry, especially in Belgian Blue (BB) cattle. This breed is naturally more predisposed to psoroptic mange but reasons for this high susceptibility remain unknown. Different immune responses could be a potential cause; thus in this study, the cutaneous immune response and in vitro cellular immune response after antigen re-stimulation were examined in naturally infested BB. Cytokine production in the skin and in circulating re-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
1
16
1
3
Order By: Relevance
“…Recently our group reported that PBMC gamma delta (γδ) + T cells increased in mange infected pigs relative to controls from as early as one week post mite infestation with these increases sustained throughout the infestation [ 88 ]. Similarly, strong PBMC proliferation of γδ + T cells was reported in cattle infested with P. ovis [ 33 ]. These peripheral blood responses mirrored cutaneous responses, with skin cell infiltrates in the lesions of CS pigs showing significantly higher γδ + T cell numbers than those with OS [ 88 ].…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Recently our group reported that PBMC gamma delta (γδ) + T cells increased in mange infected pigs relative to controls from as early as one week post mite infestation with these increases sustained throughout the infestation [ 88 ]. Similarly, strong PBMC proliferation of γδ + T cells was reported in cattle infested with P. ovis [ 33 ]. These peripheral blood responses mirrored cutaneous responses, with skin cell infiltrates in the lesions of CS pigs showing significantly higher γδ + T cell numbers than those with OS [ 88 ].…”
Section: Introductionmentioning
confidence: 68%
“…In CS, skin biopsy sections from two patients have shown large numbers of eosinophils in the dermis [ 24 ] and 58% of a cohort of CS patients were reported to have peripheral eosinophilia [ 14 ]. In Psoroptes ovis infested sheep and cattle, lesional histology studies also show an eosinophil dominated immunoinflammatory infiltrate [ 32 , 33 ]. In addition, eosinophil infiltrations have been detected in the skin dermis of red foxes infested with S. scabiei [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals vary in their immune response. Within a population, some individuals may fail to make protective immune responses following either natural infection or vaccination and so are especially vulnerable to infectious disease 14 . Defining the patterns of such variability will enhance our ability to manage the health of individuals – especially those that are most susceptible to infectious disease in human, livestock or wildlife populations.…”
Section: Introductionmentioning
confidence: 99%